THE CUMULATION OF INTELLECTUAL PROPERTY RIGHTS, WITH SPECIFIC REFERENCE TO THE CUMULATION OF PATENT AND DESIGN RIGHTS - Milosavljevic, Nikola (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
In this paper, the author primarily examines the terminology and systematics in the field of overlap of intellectual property rights, trying to determine the meaning of certain terms in this field and harmonize the terminology. Тhen he analyzes the reasons for the existence of overlaps and their permissibility. The author uses the conclusions drawn in this part for further analysis of the relationship between the patent and design right. The author performs an examination, taking into account the similarities between the mentioned rights, and taking out all the lines of coincidence. Then the differences in detail between patent and design right have been examined. The aforementioned analysis as well as analysis from general considerations were the basis for the development of further research on the possibility of overlap between patent and design right. Based on the conducted research, the author concluded that there are not enough arguments for a general prohibition of all overlaps, but that each overlap has to be specially arranged. Regarding the overlap of patent and design right, the author found that this overlap is not easily achievable, and therefore currently does not represent an excessive risk for competition, which does not mean that this will not be the case in the future.
Keywords: cumulation; convergence; colision; cumulation between patent and design right; similarities and differences between patent and design right